Personal Meaning: How is the Profile on Students? - Padmi Dhyah Yulianti; Agung Handayanto; Heri Saptadi Ismanto (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
Personal meaning in life is a crucial psychological resource that supports adaptive functioning, sustained motivation, and wellbeing during emerging adulthood. While extensively studied among employees and educators, research on university students, particularly within non-Western, collectivist, and religious contexts, remains limited. Moreover, prior studies have largely focused on predictive or mediational models, leaving the descriptive configuration of multidimensional meaning underexplored. Addressing this gap, the present study examines personal meaning profiles and gender differences among Indonesian undergraduates. Using a quantitative cross-sectional design, data were collected from 272 students through the Personal Meaning Brief Scale. Inferential analyses revealed that students reported a moderate level of overall personal meaning, with no significant gender differences. Religion emerged as the most salient source of meaning, whereas intimacy was consistently the least developed dimension. This pattern suggests an imbalanced meaning structure, in which belief-based sources develop more strongly than relational and self-transcendence-oriented meaning during emerging adulthood. The findings extend the cross-cultural aspects of personal meaning theory and highlight implications for higher education and mental health interventions. Keywords: career, mental health, personal meaning, student